Empowering Entrepreneurial Intentions: Educational Support And Self-Efficacy In MBKM Context - Lydiawati Soelaiman; Keni Keni; Ida Puspitowati (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2024)
Realizing the importance of entrepreneurship for Indonesia’s development, the Indonesian government keeps increasing the entrepreneurship ratio. One is by launching the